Implementation manual for launching and maintaining sentinel zones - Chelanga, Philemon; Gobu, Wako; Galgallo, Diba; Alulu, Vincent; Taye, Masresha; Jensen, Nathaniel D.; Fava, Francesco P. (International Livestock Research Institute, 2022)
There are several index-based drought risk financing (DRF) products available for pastoral regions, and many more new products are being proposed. These products commonly rely on indices generated from satellite-collected data as proxies for local environmental conditions, thereby avoiding costly ground-data collection for developing risk profiles, assessing local conditions, and making payments. While these index-based DRF products are promising, their accuracy and value are not guaranteed, and some ground data are required to calibrate, monitor, and assess them. Specifically, data are needed that can track the spatial and temporal dynamics between environmental conditions through household production, to household welfare, if the tools are to accurately mitigate the impacts of drought on households. Unfortunately, these data are almost entirely missing for pastoral areas in the Intergovernmental Authority on Development (IGAD) region. The sentinel zone concept was developed to meet this need by establishing a network of high-frequency and longitudinal data collection clusters specifically considering the pastoral production system and the social and environmental strata of the rangelands in the IGAD region. This manual provides guidance on how to launch and maintain a sentinel zone to those collaborating on this agenda.